Over a million students use our free study notes to help them with their homework
Label the two equations as the following: x2 + 2y = 9 y = x + 3 Equation 2 can be substituted into equation 1, giving: x2 + 2( x + 3 ) = 9Expanding the brackets and subtracting ...
You can solve simultaneous equations by either substitution or elimination. Say we have the equations:(1) 8y + 6x = 24 and (2) 2y - x = 6SUBSTITUTION METHODFirst, you need to find x in terms of y (or y in...
1. The minus sign indicates that the answer is a reciprocal meaning basically 1 over.2. Next, on inspection of the fraction, the 2 on top means that you square the number, times it by itself...
Differentiate each term in the equation separately then put then put the differentiated equation back together.First we start with (2x3):2 x 3 = 6 and 3-1=2 so we get the differentiated term of...
First rearrange x - 2y = -3 by adding 2y to each side to give x = -3 + 2ySubstitute this into the first eq. to give 3(-3 +2y) + y = 19Expand brackets first: -9 + 6y + y = 19Rearrange and simplify by colle...
←
402
403
404
405
406
→
Internet Safety
Payment Security
Cyber
Essentials